Reactivating Legislation for Organic Waste Reform in Indonesia - Nahwan, Darwin; Sukmana, Eep Jamaludin; Fikri, Ahmad Ma'mun (LifeSciFi, 2025)
Indonesia grapples with a pressing waste management crisis, generating 26.2 million tons of waste in 2023, of which 41.4% is organic, worsened by overlapping regulations and inconsistent enforcement of Law No. 18/2008 on Waste Management. This study seeks to evaluate the urgency of legislative reactivation through an Omnibus Law approach to streamline organic waste management policies and foster active participation from communities and the private sector. Using a normative juridical method, the research analyzes primary legal materials, including national laws and regulations, alongside secondary sources such as legal journals and policy reports. Findings highlight that fragmented regulations, inadequate waste processing infrastructure, and limited public awareness significantly impede effective organic waste management. The proposed Omnibus Law aims to unify disparate regulations, enhance law enforcement, and incentivize sustainable practices like composting and waste-to-energy initiatives. By addressing these challenges, the Omnibus Law can reduce environmental pollution, mitigate health risks, and support Indonesia’s sustainability goals, creating a more coordinated and efficient waste management framework.